Menghadapi Tantangan Psikologis Remaja Dengan Dzikir: Kajian Pendidikan Dalam Youtube Surat Ar-Ra’du Ayat 28-29 oleh Ustadz Dr. Musthofa Umar, Lc. MA - Rodiatul Haniah; Luthviyah Romziana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Adolescent mental health is an issue that is increasingly receiving attention, especially with the increasing cases of stress and suicide due to weak faith and social influences. This study aims to identify psychological challenges that are often faced by adolescents, analyze the benefits of dhikr in overcoming these challenges, and examine the interpretation of QS. Ar-Ra'du verses 28-29 according to Musthofa Umar and its impact on adolescent mental health. This study uses a qualitative approach with a library research method. Data were obtained from journals, books, mass media, and content analysis of Musthofa Umar's interpretation of QS. Ar-Ra'du verses 28-29. The results of the study show that psychological challenges in adolescents are influenced by family, social, and technology and social media factors. One of the solutions offered in the Qur'an is dhikr, which plays a role in calming the heart and maintaining mental balance. Musthofa Umar explains that anxiety arises due to weak faith and the drive of lust. According to him, in the letter Ar-Ra'du verse 28 dhikr can eliminate anxiety, even for those who do not fully understand the meaning of the Qur'an, because reading the word of Allah still brings peace and reward. The repetition in the verse shows that peace of mind is an ongoing process for those who always remember Allah. In addition, QS. Ar-Ra'du verse 29 emphasizes that Allah promises happiness in this world and the hereafter for those who believe and do good deeds. Therefore, dhikr not only functions as worship, but also as psychological therapy to overcome anxiety and improve the emotional well-being of adolescents.